International risk-sharing and the transmission of productivity shocks - Giancarlo Corsetti; Luca Dedola; Sylvain Leduc (European Central Bank (ECB), 2004)
A central puzzle in international finance is that real exchange rates are volatile and, in stark contradiction to effcient risk-sharing, negatively correlated with cross-country consumption ratios. This paper shows that incomplete asset markets and a low price elasticity of tradables can account quantitatively for these properties of real exchange rates. The low price elasticity stems from distribution services, intensive in local inputs, which drive a wedge between producer and consumer prices and lower the impact of terms-of-trade changes on optimal agents' decisions. Two very different patterns of the international transmission of productivity improvements generate the observed degree of risk-sharing: one associated with a strengthening, the other with a deterioration of the terms of trade and real exchange rate. Evidence on the effect of technology shocks to U.S. manufacturing, identified through long-run restrictions, is found in support of the first transmission pattern, questioning the presumption that terms-of-trade movements foster international risk-pooling.
Keywords: F32; F33; F41; 330; consumption-real exchange rate; distribution margin; incomplete asset markets